Suffering and Evil - John B Chethimattam (Journal of Dharma, 2020)
Human suffering was one of the rnam points of depar- ture for the religious quest in several traditions. Why should man, seeker of good and of ultimate happiness, actually find himself in constant suffering? Even today it remains the main hu- man focus of religions. What do religions provide as solutions to this problem of human suffering? This is the theme we have chosen for this issue of the Journal of Dharma. Besides being a deep metaphysical! problem, suffering has also psychological, social and cultural implications. It is a cen- tral theme in numerous works of art, down the centuries. Man has tried to depict his tragic condition in marble and paint, as well as in immortal works of tragic drama and poetry. But in these he has also expressed his capacity to survive the greatest tragedies of nature and to retain his personal life and dignity. The earliest signs of human artistic creativity appear in the burial places, where he has depicted in unmistakable symbols his be- lief in the immortal survival of the departed.